Marchando pelo arco-íris da política - Silva, Alessandro Soares da (2006)
This doctoral dissertation in Social Psychology is an intercultural study with a Political Psychology approach about the construction of the collective political consciousness of homosexuals in Brazil, Spain and Portugal beginning with the participation in the LGBT Pride Parade in each country. The LGBT Pride Parade is a mass phenomenon, a psychopolitical strategy of constructing an active citizenship of these subjects. Thus the parade functions as an instrument of bringing back the political memory of homosexuals and as a form of becoming visible in an assimilationist and hetero-normative society adverse to differences. The process of composition of this dissertation implied the conducting of field work in these three countries between 2003-2006 that resulted in 44 interviews of militants of the respective LGBT movements and of militant homosexuals in other movements and political parties. We used open interviews as our methodology and a form of free association of words with the intent of understanding the socio-historical process of each national context in other to conduct the intercultural study. The data show how political participation mediates the construction of the political subject and the collective subject. The festive elements and protest elements in more traditional forms mix in the process of the political construction of the movements themselves that act as an questioning element of the structures established aprioristically according to the interests of the dominant groups